2020
DOI: 10.1136/gutjnl-2020-320926
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, clinical and virological characteristics of 74 cases of coronavirus-infected disease 2019 (COVID-19) with gastrointestinal symptoms

Abstract: To cite: Jin X, lian J-s, hu Jh, et al. Gut epub ahead of print: [please include Day Month Year].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
1,167
11
96

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,183 publications
(1,367 citation statements)
references
References 27 publications
47
1,167
11
96
Order By: Relevance
“…A total of 15 papers that analyzed the clinical experience with the COVID-19 infection that also reported the presence of gastrointestinal symptoms, were identified. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Thirteen papers were from China, 5-13, 15-17, 19 one from Singapore, 18 and one from the World Health Organization European Region. 14 (Table 1) These papers analyzed a total of 2800 patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 15 papers that analyzed the clinical experience with the COVID-19 infection that also reported the presence of gastrointestinal symptoms, were identified. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Thirteen papers were from China, 5-13, 15-17, 19 one from Singapore, 18 and one from the World Health Organization European Region. 14 (Table 1) These papers analyzed a total of 2800 patients.…”
Section: Resultsmentioning
confidence: 99%
“…And in the majority of the cases, was self-limited. 10 In terms of epidemiological factors related to the presence of GI symptoms, Chen N et al, reported that 49% of their 99 patients had a history of exposure to the Huanan seafood market, from where the first cases of COVID-19 appeared to raise. 6 However, they did not report if this epidemiological factor was related or not with the presence of gastrointestinal symptoms or any other clinical manifestation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…in addition to COVID-19. Regarding the gastrointestinal symptoms, we now have enough data mentioning gastrointestinal (GI) symptoms like diarrhea, nausea, and vomiting as presenting symptoms for COVID-19 disease [5]. This GI symptomatology of COVID-19 can easily be confused with other differentials like acute graft-versus-host disease, CMV colitis, mucositis, etc.…”
Section: The Daunting Task Of Differentiating Covid-19 From Other Oppmentioning
confidence: 99%
“…(1) De esta manera, en época de pandemia por COVID-19, como cirujanos quedamos expuestos sin la protección adecuada ante pacientes que se presenten en urgencias con cuadros gastrointestinales de COVID-19 y leves o ningún síntoma pulmonar; hasta un 10% presentan radiografías de tórax sin neumonía como en el caso expuesto. (2) Consideramos que deberían replantearse los protocolos y nos cuestionamos si los tests de entrada masivos hubieran permitido un mejor triaje y tratamiento de los pacientes atendidos desde urgencias, evitando que se extendiera la infección. Ante la sospecha por el contexto epidemiológico, hay datos que se han expuesto en el caso que nos ayudaron a pensar en la posibilidad de COVID-19 y que su inmediatez permite avanzar en el diagnóstico y aislamiento del paciente.…”
Section: Respuesta Autores A: a Propósito De La Carta Científica "Sosunclassified